The Importance of Genomic Literacy and Education in Nursing - Majstorović, Dijana; Barišić, Anita; Štifanić, Mauro; Dobrača, Igor; Vraneković, Jadranka (Frontiers in Genetics, 2021)
Genetic discoveries and technological advances have been changing nursing care delivery, which modifies the roles and practices of nursing in society. Although the need for education of nurses in the field of genomics has been recognized in the 1960s, many countries still have no clear guidelines in this field of education and training. The purpose of this study was to evaluate current genomics content in the curriculum of undergraduate and graduate programs of studies in nursing in Croatia, and to measure the genomic literacy of Croatian undergraduate nursing students through assessing participants’ understanding of genomic concepts most critical to nursing practice. The curriculum of undergraduate and graduate programs of nursing classes of 2020/2021 were independently analyzed by the authors. For measuring the knowledge of essential genomic concepts among nurses, a Genomic Nursing Concept Inventory (GNCI©) instrument was employed. Results indicate that the current genomics content, for undergraduate and graduate nursing programs in Croatia, is inadequate and not concordant among universities. Moreover, the genomic literacy of Croatian undergraduate students (Undergraduate program 10) was found to be low. Scores across respondents ranged from 3 to 22 (out of possible 31), with a mean scale score 9.8 (SD 5.3) (31.6% correct). We can conclude that the curriculum for undergraduate and graduate programs of Studies in nursing should be revised to implement the latest genomic practices and approaches to genomics education while nurses should acquire an adequate level of genomic literacy in order to produce desired outcomes of competency in nursing practice.